Influence of Birth Preparedness, Decision-Making on Location of Birth and Assistance by Skilled Birth Attendants among Women in South-Western Uganda - Kabakyenga, Jerome K.; Ostergren, Per-Olof; Turyakira, Eleanor; Pettersson, Karen O. (PloS one, 2012)
Introduction: Assistance by skilled birth attendants (SBAs) during childbirth is one of the strategies aimed at reducing maternal morbidity and mortality in low-income countries. However, the relationship between birth preparedness and decision-making on location of birth and assistance by skilled birth attendants in this context is not well studied. The aim of this study was to assess the influence of birth preparedness practices and decision-making and assistance by SBAs among women in south-western Uganda. Methods: Community survey methods were used to identify 759 recently delivered women from 120 villages in rural Mbarara district. Interviewer-administered questionnaires were used to collect data. Logistic regression analyses were conducted to assess the relationship between birth preparedness, decision-making on location of birth and assistance by SBAs. Results: 35% of the women had been prepared for childbirth and the prevalence of assistance by SBAs in the sample was 68%. The final decision regarding location of birth was made by the woman herself (36%), the woman with spouse (56%) and the woman with relative/friend (8%). The relationships between birth preparedness and women decision-making on location of birth in consultation with spouse/friends/relatives and choosing assistance by SBAs showed statistical significance which persisted after adjusting for possible confounders (OR 1.5, 95% CI: 1.0–2.4) and (OR 4.4, 95% CI: 3.0–6.7) respectively. Education, household assets and birth preparedness showed clear synergistic effect on the relationship between decision-maker on location of birth and assistance by SBAs. Other factors which showed statistical significant relationships with assistance by SBAs were ANC attendance, parity and residence. Conclusion: Women’s decision-making on location of birth in consultation with spouse/friends/relatives and birth preparedness showed significant effect on choosing assistance by SBAs at birth. Education and household assets ownership showed a synergistic effect on the relationship between the decision-maker and assistance by SBAs.
Keywords: skilled birth attendants; childbirth; Women